Effect of Cooperative Membership on Performance of Farmers: Evidence of Cereal Farmers from Plain Region (Terai) of Nepal - Kharel, Suman; Neupane, Huma; Adhikari, Mandeep; Regmi, Kamal (Tribhuvan University Journal, 2023)
Developing cooperatives is one of the important approaches to improve the farmer’s performance. In this paper we used the data collected from western plain of Nepal and applied an endogenous switch regression model in order to study the relationship of farmers’ membership in cooperative with benefit cost ratio of rice and wheat production. The findings show high benefit cost ratio for cooperative farmers in both rice and wheat. The findings also reveal higher amount of inputs use among the cooperative farmers as compared to the non-cooperative farmers. The disaggregation based on land area shows that farmers with small landholdings are more benefited from cooperative however cooperative membership evidence is more in farmers with higher land holdings. Our findings highlight that smallholdersshould be provided with assistance to be involved in cooperatives for higher benefit from cereal farming.